2005
DOI: 10.1007/s11010-005-5905-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of p53 attenuates doxorubicin-induced cardiac toxicity in mice

Abstract: Use of the chemotherapeutic agent doxorubicin (Dox) is limited by dose-dependent cardiotoxic effects. The molecular mechanism underlying these toxicities are incompletely understood, but previous results have demonstrated that Dox induces p53 expression. Because p53 is an important regulator of the cell birth and death we hypothesized that targeted disruption of the p53 gene would attenuate Dox-induced cardiotoxicity. To test this, female 6-8 wk old C57BL wild-type (WT) or p53 knockout (p53 KO) mice were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 40 publications
10
101
0
2
Order By: Relevance
“…Promotion of p53 activity, already shown in other biological contexts, is prompted by nucleolar stress in an early cellular response preceding p53 activation and the induction of a suicide signal program (1,3,4,26,27). Although the importance of multiple pathways to explain DOX-mediated pathogenesis should not be underestimated, data presented herein implicate nucleolar stress as an important mechanism of DOX cardiotoxicity and corroborate reports that DOX cardiotoxic effects are ameliorated by p53 inhibition (37)(38)(39).…”
Section: Discussionsupporting
confidence: 87%
“…Promotion of p53 activity, already shown in other biological contexts, is prompted by nucleolar stress in an early cellular response preceding p53 activation and the induction of a suicide signal program (1,3,4,26,27). Although the importance of multiple pathways to explain DOX-mediated pathogenesis should not be underestimated, data presented herein implicate nucleolar stress as an important mechanism of DOX cardiotoxicity and corroborate reports that DOX cardiotoxic effects are ameliorated by p53 inhibition (37)(38)(39).…”
Section: Discussionsupporting
confidence: 87%
“…It had been suggested that up-regulated Bax protein and down-regu-lated Bcl-2 protein activated the apoptotic pathway (Zhu et al, 2015;Gupta and Knowlton, 2005). In the cardiovascular system, p53 or Bax-mediated signaling pathway in the apoptosis of cardiomyocytes was recently shown to have a crucial function in the development of HF (Shizukuda et al, 2005;Qin et al, 2006). In our study, we found that PM 2.5 exposure up-regulates p53, Bax and Caspase-1 protein in cardiac tissues and decreases the expression of Bcl-2, while the ratio of Bcl-2/Bax is also increased.…”
Section: Discussionmentioning
confidence: 99%
“…38 p53 knockout mice are associated with reduced doxorubicin-induced myocardial dysfunction. 39 Thus, the increase of senescence-associated molecules may be involved in the cardiac dysfunction of db/db mice, and candesartan may improve cardiac function, in part, by reducing the amount of these senescenceassociated molecules.…”
Section: Discussionmentioning
confidence: 99%